2018
DOI: 10.12911/22998993/91268
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substrates Used for Green Roofs in Limiting Rainwater Runoff

Abstract: The retention of rainwater is one of the main functions of green roofs in urban areas. One of the elements influencing the variability of rainwater retention on green roofs is the configuration of the roof, i.e. the combination of drainage and vegetation layers and plants. In the article, laboratory studies regarding the influence of the vegetation layer of the green roof on the retention of rainwater were carried out, and the influence of changes in the initial moisture content in extensive and intensive subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
4
13
1
Order By: Relevance
“…Source: own study. Similarity to studies regarding the retention ability of green roofs and retention ability of substrates [BARYŁA et al 2018b], decreases along with an increase in the rainfall depth (Fig. 3].…”
Section: Results Of Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Source: own study. Similarity to studies regarding the retention ability of green roofs and retention ability of substrates [BARYŁA et al 2018b], decreases along with an increase in the rainfall depth (Fig. 3].…”
Section: Results Of Studiessupporting
confidence: 86%
“…These systems copy the relationships taking place between a natural catchment, returning the imbalanced proportions between the processes of retention, infil-tration, transpirations and decontamination with the use of plants. Green roofs play a significant role in sustainable drainage systems [BARYŁA et al 2018b;BUS et al 2016;PALLA et al 2010;PĘCZKOWSKI et al 2018;SOBCZYK, MROWIEC 2016;VILLARREAL, BENGTSSON 2005]. In addition to hydrological abilities, green roofs decrease the effect of urban heat islands [WONG, JIM 2015], decrease energy usage by cooling the roof in the summer period [BANTING et al 2017], create a habitat for plants and animals, thus improving urban biodiversity [CATALANO et al 2018;EMILSSON et al 2007;KÖHLER 2006], improve the aesthetics of cities [BENGTSSON et al 2005;STOVIN et al 2012;SZOTA et al 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the value of (C) may vary depending on the slope of the green roof, the thickness of the substrate layer and the type of vegetation, as well as the amount of water accumulated in its structure prior to the rain event [63]. The hydrological response of roofs is also influenced by the function of its configuration, with the substrate or growing media [64], and with the combination of drainage and vegetation layers [51].…”
Section: Green Roof Efficiency-expected Retentionmentioning
confidence: 99%
“…The type of substrate and its depth play an important role in green roofs [26,27]. The substrate is a specific and modified mixture, which is usually lighter than soil, porous, mainly inorganic and capable of sustaining plant growth [28,29]. The depth of the substrate can range from a few centimetres to a metre.…”
Section: Introductionmentioning
confidence: 99%